2001
DOI: 10.1093/emboj/20.9.2152
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric interactions between GB1 andGB2 subunits are required for optimalGABAB receptor function

Abstract: T.Galvez and B.Duthey contributed equally to this workRecent studies on G-protein-coupled receptors revealed that they can dimerize. However, the role of each subunit in the activation process remains unclear. The g-amino-n-butyric acid type B (GABA B ) receptor is comprised of two subunits: GB1 and GB2. Both consist of an extracellular domain (ECD) and a heptahelical domain composed of seven transmembrane a-helices, loops and the C-terminus (HD). Whereas GB1 ECD plays a critical role in ligand binding, GB2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
325
1
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(347 citation statements)
references
References 36 publications
18
325
1
3
Order By: Relevance
“…We previously reported that the insertion of these tags after the signal peptide, and before the Venus fly trap (VFT) ligand binding domain does not alter functional properties of class C GPCRs (both mGlu and GABAb receptors) (Ango et al, 2000;Galvez et al, 2001;Havlickova et al, 2002;Hlavackova et al, 2005;Pagano et al, 2001). We used wild type receptors where possible in order to verify results obtained with our N-terminally tagged proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that the insertion of these tags after the signal peptide, and before the Venus fly trap (VFT) ligand binding domain does not alter functional properties of class C GPCRs (both mGlu and GABAb receptors) (Ango et al, 2000;Galvez et al, 2001;Havlickova et al, 2002;Hlavackova et al, 2005;Pagano et al, 2001). We used wild type receptors where possible in order to verify results obtained with our N-terminally tagged proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Constructs HA-mGluR1 and HA-GB1a and HA-GB2 were used and described in our previous studies (Ango et al, 2000;Galvez et al, 2001;Havlickova et al, 2003;Hlavackova et al, 2005;Pagano et al, 2001). MGluR1b variant was tagged using the same strategy.…”
Section: 1mutagenesismentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, seule la sous-unité GABA B1 lie le GABA, alors que GABA B2 est nécessaire à l'activation des protéines G [5,6], indiquant un fonctionnement asymétrique d'un dimère de RCPG, décrit depuis pour d'autres RCPG hétérodimériques, mais aussi homodimériques [7]. Chacune de ces sous-unités est constituée d'un Les récepteurs couplés aux protéines G (RCPG) sont des acteurs importants de la communication cellulaire.…”
Section: à Deux Sinon Rien : L'hétérodimère Comme Entité Fonctionnellunclassified
“…À l'image de celui proposé pour les autres RCPG de la classe C, et notamment pour les récepteurs métabotropes du glutamate (mGlu), l'activation des messagers intracellulaires en réponse à la liaison de l'agoniste dans le domaine extracellulaire du récepteur provient de changements de conformation importants au sein du dimère [11,12]. Dans le cas du récepteur GABA B , si l'activation est initiée par la liaison du GABA dans le VFT de la sous-unité GABA B1 et la fermeture de ce domaine [13], la stimulation des cascades de signalisation, et notamment des protéines G, requiert des changements de conformation au sein du domaine membranaire de GABA B2 [6,14]. La transmission conformationnelle au sein de l'hétérodimère, depuis la fermeture du domaine VFT de GABA B1 vers le domaine membranaire de GABA B2 , se produit par deux voies concomitantes (Figure 2).…”
Section: à Deux Sinon Rien : L'hétérodimère Comme Entité Fonctionnellunclassified